Another Look at the Impacts of Health Reform in Massachusetts: Evidence Using New Data and a Stronger Model - Long, Sharon K; Stockley, Karen; Yemane, Alshadye (American Economic Review, 2009)
In April 2006, Massachusetts enacted a comprehensive health care reform bill that seeks to move the state to near universal insurance coverage. The bill included expanded eligibility for public coverage, subsidized insurance, market reforms, requirements for employers, and, most controversial, an individual mandate. A study of the early impacts of the state's initiative found evidence of a substantial drop in uninsurance–from 13 to 7 percent for nonelderly adults (Long 2008). Because that study relied on a simple pre-post comparison, it is possible that the estimates of the impact of health reform reflect both the changes under health reform and factors beyond health reform that changed over the same period, leading to biased estimates of the impacts of reform (Lawrence B. Mohr 1995). This paper expands on the earlier work to estimate the impacts of health reform in Massachusetts using new data and a stronger research design. Specifically, we rely on data over time for Massachusetts and other states from the Current Population Survey (CPS) to estimate difference-in-differences (DD) models (Jeffrey M. Wooldridge 2002).